A feasibility study using an array of LaBr3(Ce) scintillation detectors as a Compton camera for prompt gamma imaging during BNCT - Nutter, Kiran; Price, Tony; Kokalova, Tzany; Green, Stuart; Phoenix, Ben (Frontiers in Physics, 2024)
Boron Neutron Capture Therapy (BNCT) is a binary cancer therapy where a low energy neutron beam is incident upon a patient who has been administered a tumour-seeking 10 B loaded compound. The neutron capture reaction on 10 B results in the production of two short range particles, 7 Li and 4 He, that deposit all of their energies within the targeted cell. However, accurate, online dosimetry during BNCT is challenging as it requires knowledge of both the neutron fluence and 10 B concentration in cells. An additional product in the neutron capture reaction on 10 B is a 478 keV prompt gamma ray, and if the production vertices of these gamma rays could be imaged by an external camera, the density of the vertices could be used to infer the dose delivered to the patient. In this study, the feasibility of using an array of LaBr 3 scintillators as a modified Compton camera for prompt gamma imaging during BNCT was investigated using Geant4 simulations.These simulations demonstrated that a phantom containing a 3 cm diameter region of 400 ppm 10 B could be reconstructed using clinically relevant neutron fluences. This result opens up more possibilities for future research to improve dosimetry during BNCT.